Pengaruh Profitability, Free Cash Flow, Dan Leverage Terhadap Earnings Management - Cindy Calista, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2021)
This research aims at how the role of the board of profitability, free cash flow, and leverage on earnings management on consumer goods industry and basic chemical industry listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 46 companies. Data processing techniques using multiple regression analysis what helped by Eviews 11 and Microsoft Excel 2016. The results of this study indicate that the profitability and leverage have a negative significant effect on the earnings management, free cash flow does not have a significant effect on the earnings management. The implication of this study is the lower the profitability, the greater the probability of earnings management, the higher the leverage, the lower the probability of earnings management, while free cash flow does not have a significant effect on earnings management.